Epigenetic changes in cancer - Esteller, Manel (Faculty of 1000 Ltd, 2011)
Interest in epigenetics is now booming in all the biomedical fields. Initially, interest was sparked within the field of cancer research with the finding of global DNA hypomethylation events in the 1980s, followed by the CpG island hypermethylation of tumor suppressor genes in the 1990s and the approval of DNA demethylating drugs and histone deactylase inhibitors in the 2000s. For transformed cells, the arena is also expanding to include the wide spectrum of histone modification changes and the interaction with noncoding RNAs. What lies ahead is even more exciting, with the imminent completion of many human cancer epigenomes that will form the basis of better biomarkers and epigenetic drugs.